Assessment of Knowledge, Associated Factors and Prevalence of Health Problems Related to Usage of Mobile Phones among a Population of 2nd and 3rd Year Undergraduates in University of Sri Jayewardenepura; A Cross Sectional Study - Lasanthika, T.L.C.; Hettiaratchi, U.P.K. (Proceedings of 9th International Research Conference, KDU, Sri Lanka, 8th-9th Sept 2016, 2016)
Attached

Over usage of mobile phones and addiction are emerging challenges to the public health worldwide. It has vastly affected the life style of the people and caused some behavioral changes. Thus, this study aimed to assess the knowledge, associated factors and prevalence of health problems related to usage of mobile phones among a selected population of university students in University of Sri Jayewardenepura. This study involved 384 randomly selected 2nd and 3rd year undergraduates who completed the pre-tested self-administered questionnaire. The statistical analysis was done using International Business Machines Corporation (IBM) statistics SPSS version 21.0 software. The study group consisted of 121(32.5%) males and 251(67.5%) females. Response rate was 96.9%. The mean age was 23±lyear. Majority of the students demonstrated a good knowledge regarding usage and adverse health effects of mobile phones. 83.1% students were moderately addicted to their mobile phones while 5.1% students were severely addicted. Significantly higher mobile phone addiction level showed incidence of some health problems such as headache, body ache, ear ache, irritability/restlessness, sleep disturbances, hearing defects while or after using mobile phone among the study subjects (P<0.05). Significant relationships were found between high mobile phone addiction level and unable to understand lectures as well as feeling memory loss among study participants (P<0.05). This study serves as an evidence-based background to make the public aware regarding potential health risks related to mobile phone over usage and the need to educate the public to depend less on the device.
Keywords: Health problems; Mobile phone usage; Undergraduates